THE EFFECT OF OWNERSHIP STRUCTURE AND SUSTAINABILITY REPORT DISCLOSURE TOWARD COMPANY VALUE WITH FINANCIAL PERFORMANCE AS INTERVENING VARIABLE - Rusyda, Zahra Tiara; Priantinah, Denies (Universitas Negeri Yogyakarta, 2018)
This research aims to know the effect of Ownership Structure and Sustainability Report Disclosure toward Company Value with Financial Performance as Intervening Variable on companies that publish Sustainability Report during 2013-2016. Research design was a causative research. The data population taken from companies publish Sustainability Report and listed in Indonesia Stock Exchange (IDX) during 2013-2016. Sampling method used in this research is purposive sampling. There were 10 companies that fulfilled the sample criterias. So, the data sample in this research were 40. Analysis techniques consisted of multiple regression analysis and path analysis. The result of this research showed that (1) Managerial Ownership directly effects Company Value, (2) Institutional Ownership does not directly effect on Company Value, (3) Sustainability Report Disclosure does not directly effect on Company Value, (4) Managerial Ownership indirectly effects on Company Value with Financial Performance as an intervening variable, (5) Institutional Ownership does not indirectly effect Company Value with Financial Performance as an intervening variable, (6) Sustainability Report Disclosure indirectly effects on Company Value with Financial Performance as an intervening variable. Keywords: Managerial Ownerhsip, Institutional Ownership, Sustainability Report, Financial Performance, and Company Value